2005
DOI: 10.1161/circulationaha.104.511998
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Coronary Heart Disease

Abstract: Background-Results from studies relating periodontal disease to cardiovascular disease have been mixed. Residual confounding by smoking and use of clinical measures of periodontal disease rather than measures of infection have been 2 major criticisms. The aims of this study were to investigate relationships between prevalent coronary heart disease (CHD) and 2 exposures, (1) clinical periodontal disease and (2) IgG antibodies to 17 oral organisms, and to evaluate the role of smoking in these relationships. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 289 publications
(122 citation statements)
references
References 52 publications
7
114
1
Order By: Relevance
“…In a population-based study conducted for 45 to 64 year-olds in the United States, a high serum IgG antibody level to P. intermedia was associated with risk of CHD among never smokers. 32) A relationship between P. intermedia and CHD was only detected in subjects aged 56-69 years in this study. This might be linked to the fact that P. intermedia play a major role during chronic periodontitis, with which older people are more likely to be afflicted, by regulating diverse inflammatory and immune responses to tissue destruction.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In a population-based study conducted for 45 to 64 year-olds in the United States, a high serum IgG antibody level to P. intermedia was associated with risk of CHD among never smokers. 32) A relationship between P. intermedia and CHD was only detected in subjects aged 56-69 years in this study. This might be linked to the fact that P. intermedia play a major role during chronic periodontitis, with which older people are more likely to be afflicted, by regulating diverse inflammatory and immune responses to tissue destruction.…”
Section: Discussioncontrasting
confidence: 43%
“…Similarly, several studies showed no significant connection between the presence of IgG antibodies to P. gingivalis and CHD, especially after adjusting for confounding variables. 15,32,35) In spite of the similar infectious capability of P. gingivalis strains, the risk of CHD differs depending on the strain; a particular genotype of P. gingivalis with strong virulence is considered to be involved more in the mechanisms linking periodontitis and CHD. 16) The existence of different genotypes of P. gingivalis with different virulence may also contribute to the inconsistent relationship with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanism for the association of 8-isoprostane concentrations with decreased IgG antibody levels, it will be necessary to define better the specific mediators of lipid-based redox signaling, specific cellular and molecular targets, and correlations of IgG subclass antibody levels (and antibody isotypes) to serum 8-isoprostane concentrations. It is expected that clinical and mechanistic insights from these investigations will enable interventions that better target populations and mechanisms likely to have impact on the systemic diseases that have been associated with systemic exposure to the mucosal biofilm microflora (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these clinical conditions tend to be associated with increases in serum antibody titers to specific organisms within the biofilm, presumably as a consequence of bacterial presentation via tissue invasion or penetration of the organism, or components such as LPS. These systemic antibodies presumably also have a role in clearing bacteremias (1,3) associated with systemic exposure to the oral microbes, a possible risk factor for systemic diseases (5,6).…”
mentioning
confidence: 99%
“…People who have the hyperinflammatory monocyte phenotype secrete from three to ten times more mediators in response to bacterial lipopolysaccharides, when compared with people who are phenotypically normal. 50 According to Seymour and Steele, 51 there is evidence that patients with aggressive forms of periodontitis have this hyperinflammatory phenotype. Thus, the interaction between bacterial lipopolysaccharides and the monocytes that release a range of different cytokines is fundamental to initiation and progression of PD and also to its systemic effects, such as atherogenesis and thrombogenesis.…”
Section: Pathophysiology Of Periodontal Diseasementioning
confidence: 99%